Almost Conservative Four-Dimensional Matrices through de la Vallée-Poussin Mean - S. A. Mohiuddine; Abdullah Alotaibi (Abstract and Applied Analysis)
The purpose of this paper is to generalize the concept of almost convergence for double sequence through the notion of de la Vallée-Poussin mean for double sequences. We also define and characterize the generalized regularly almost conservative and almost coercive four-dimensional matrices. Further, we characterize the infinite matrices which transform the sequence belonging to the space of absolutely convergent double series into the space of generalized almost convergence.